Abundance and distribution patterns of Jack mackerel Trachurus murphyi in Peru - Dioses, Teobaldo (2013)
This paper analyzes information from IMARPE bio-oceanographic surveys conducted between 1961 and 2011 covering an area from 0 to 100 nm from the coast with observations at depths from 0 to 180 m; information from scientific observers on board Peruvian, Soviet and Cuban factory trawlers operating between 1983 – 1998; as well as time series of sea surface temperature anomalies, depth of the 15 °C isotherm and sea surface salinity from 1950 to date. Three patterns in the vertical distribution and depth of catches of Jack mackerel Trachurus murphyi are identified and described in relation to changing environmental conditions: (1) During strong El Niño (EN) events shoals are at depths between 100 – 200 m, catches are higher and don’t change much between day and night; (2) During strong upwellings shoals are shallower, at depths between 0 – 75 m and catches are more oceanic (offshore) and closer to the surface; and, (3) When there is a strengthen Southern Extension of the Cromwell Current (SECC) shoals are at depths between 0 and 300 m, fishing takes place closer to the coast being deeper during the day and shallower during the night. During cold periods there is lower abundance of T. murphyidue to the prevalence of Cold Coastal Waters (CCW) and the offshore shift of the Subtropical Surface Waters (SSW), while abundance is higher during warmer periods associated with EN events and the strengthening of the SECC. A certain latitudinal segregation by sizes in relation to the Pacific Decadal Oscillation is also observed.